2015
DOI: 10.1002/14651858.cd007017.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical policies: effects of cap and co-payment on rational use of medicines

Abstract: The diversity of interventions and outcomes addressed across studies and differences in settings, populations and comparisons made it difficult to summarise results across studies. Cap and co-payment polices may reduce the use of medicines and reduce medicine expenditures for health insurers. However, they may also reduce the use of life-sustaining medicines or medicines that are important in treating chronic, including symptomatic, conditions and, consequently, could increase the use of healthcare services. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 131 publications
2
63
0
6
Order By: Relevance
“…This likely explains why prescription drug coverage has previously and, in recent literature, continues to be positively associated with medication adherence. In contrast, a lack of medication coverage is negatively associated with adherence [3234]. Consistent with these observations, Choudhry et al demonstrated that eliminating copayments for medications resulted in a 4–6% absolute increase in rates of medication adherence ( P < 0.001) [35].…”
Section: Socioeconomic Factorsmentioning
confidence: 96%
“…This likely explains why prescription drug coverage has previously and, in recent literature, continues to be positively associated with medication adherence. In contrast, a lack of medication coverage is negatively associated with adherence [3234]. Consistent with these observations, Choudhry et al demonstrated that eliminating copayments for medications resulted in a 4–6% absolute increase in rates of medication adherence ( P < 0.001) [35].…”
Section: Socioeconomic Factorsmentioning
confidence: 96%
“…Of these, 11 were Cochrane Reviews (Akbari 2008; Haynes 2008; Lagarde 2009; Lagarde 2011; Scott 2011; Witter 2012; Acosta 2014; Rutebemberwa 2014; Grobler 2015; Luiza 2015; Lutge 2015). The dates of the most recent search reported in the included reviews ranged from February 2007 in Haynes 2008 to June 2015 in Lutge 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Four reviews had no included studies from a low- or middle-income country (Scott 2011; Acosta 2014; Grobler 2015; Luiza 2015), while six reviews included only studies conducted in low- and middle-income countries (Lagarde 2009; Carr 2011; Hayman 2011; Lagarde 2011; Acharya 2012; Witter 2012). Four reviews included studies from a mix of low-, middle- and high-income countries (Akbari 2008; Haynes 2008; Brody 2013; Lutge 2015) .One review did not have any included studies (Rutebemberwa 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors explain this as an improvement in responsible use of medicines 5 6. However, very few studies have explored the effect of copayment policies on health outcomes and the long-term impact of these outcomes on health expenditure 7. Furthermore, copayment policy design may create healthcare inequities by imposing a higher relative burden on low-income patients 8 9…”
Section: Introductionmentioning
confidence: 99%